Penyimpangan Penafsiran dalam Tafsīr Al-Tha’labī dan Al-Kashshāf Menurut Muḥammad Ḥusayn Al-Dhahabī - Ali Thaufan Dwi Saputra (Refleksi, 2020)
This article reviews the conception of interpretation deviation according to Ḥusayn al-Dhahabī. According to him, many interpreters have certain motives for making deviations in interpreting the Qur’an. Broadly speaking, al-Dhahabī conceptualizes mis-interpretation into two things. First, the interpreters who tend to overtake Isrāiliyāt history excessively, this occurs in the tafsir bi al-ma’thūr. Second, interpreters who interpret verses with incorrect meanings, this happens in tafsir bi al-ra’yi. This second deviation is often done by mufasirs who have certain mazhab background and Sufis due to their use metaphorical language. The findings of this article are, al-Dhahabī considers that there are some deviations in the interpretation of the Quran in the book of al-Kashfu wa al-Bayān an Tafsīr al-Qur’ān by Abū Isḥāq Aḥmad ibn Ibrāhīm al-Tha’labī al-Naisaburī and al-Kashshāf ‘An Ḥaqā’iq Ghamāmi al-Tanzīl wa ‘Uyūn al-Aqawīl fī Wujūh al-Ta’wīl by Abū al-Qasīm Maḥmūd ibn ‘Umar Ibn Muḥammad Ibn ‘Umar al-Zamakhsharī. Some interpretations of al-Tha’labī are considered to be distorted due to a number of quotes from the history of Isrāiliyāt. On the other hand, some interpretations of al-Zamakhsharī are considered to be distorted because they distort the meaning and bias of the mazhab.